2014
DOI: 10.1186/2051-5960-2-53
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation in multiple sclerosis plaques: an immunohistochemical analysis

Abstract: IntroductionInflammation and complement activation are firmly implicated in the pathology of multiple sclerosis; however, the extent and nature of their involvement in specific pathological processes such as axonal damage, myelin loss and disease progression remains uncertain. This study aims to bring clarity to these questions.ResultsWe describe a detailed immunohistochemical study to localise a strategically selected set of complement proteins, activation products and regulators in brain and spinal cord tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
127
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 34 publications
13
127
0
1
Order By: Relevance
“…High levels of immunoglobulins and C5b-9 deposition at sites of active myelin destruction are characteristic for pattern II MS lesions and C5–9 deposits are present only in this type of demyelinating lesion [2, 8]. In chronic MS, plaques are found to be consistently positive for complement proteins (C3, factor B, C1q), activation products (C3b, iC3b, C4d, terminal complement complex) and inhibitors (factor H, C1-inhibitor, clusterin), suggesting that there is continuing local complement synthesis, activation, and regulation despite the absence of other evidence of ongoing inflammation [9]. An initial heterogeneity of demyelinating lesions in the earliest phase of MS lesion formation [2] may disappear over time as different pathways converge in one general mechanism of demyelination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of immunoglobulins and C5b-9 deposition at sites of active myelin destruction are characteristic for pattern II MS lesions and C5–9 deposits are present only in this type of demyelinating lesion [2, 8]. In chronic MS, plaques are found to be consistently positive for complement proteins (C3, factor B, C1q), activation products (C3b, iC3b, C4d, terminal complement complex) and inhibitors (factor H, C1-inhibitor, clusterin), suggesting that there is continuing local complement synthesis, activation, and regulation despite the absence of other evidence of ongoing inflammation [9]. An initial heterogeneity of demyelinating lesions in the earliest phase of MS lesion formation [2] may disappear over time as different pathways converge in one general mechanism of demyelination.…”
Section: Introductionmentioning
confidence: 99%
“…C1q staining is present in all plaques, suggesting a dominant role for the classical pathway. Cellular staining for complement components is largely restricted to reactive astrocytes, often adjacent to clusters of microglia that are in close apposition to complement-opsonized myelin and damaged axons [9]. We have previously shown that astrocytes in culture can secrete most of the complement proteins and expression is markedly enhanced by TNFα, IL-1β and IL-8 [10].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] Regarding reports that oligodendrocyte apoptosis and complementpositive myelin are not seen together in MS lesions but only in tumefactive NMO, 25 in our own studies of prephagocytic and actively demyelinating MS lesions, we have never observed commencing myelin breakdown by macrophages where myelin sheaths are not opsonized by complement or where macrophages stain negatively for complement. Affected sheaths have been observed to stain positively for IgG and kappa and lambda light chains, but this is rare and always difficult to demonstrate.…”
Section: Discussionmentioning
confidence: 70%
“…The complement system is a key component of innate immunity [8] and has been implicated in the pathogenesis of inflammatory [9][10][11] and neurodegenerative diseases [12][13][14][15][16], indicating that complement may be a good target to slow, halt or reverse both processes. Notably, a role for complement in MS has been suggested based upon evidence that complement is activated and deposited in the MS brain [17][18][19][20][21][22][23], and it is a critical effector in the acute experimental autoimmune encephalomyelitis model of the disease [24][25][26][27]. However, the extent and nature of complement activation and its contribution to the progressive phase of the disease remain controversial and difficult to investigate in acute models that do not replicate the natural course of the human disease.…”
Section: Introductionmentioning
confidence: 99%